MEASURES OF THE COURT OF AUDITORS - RELATION OF THE COURT OF AUDITORS - AUDITEES. PREREQUISITES FOR COMMITTING THE OFFENCE PROVIDED FOR IN ART. 64 OF LAW NO. 94/1992 IN "CO-AUTHORSHIP” - Ionela-Alina ZORZOANĂ (Challenges of the Knowledge Society)
The scope of the study is to analyse the Regulation on the organisation and conduct of specific activities of the Court of Accounts, as well as the use of documents resulting from these activities (RODAS)I from the perspective of the relationship between the audit authority and the auditee, in relation to the offence provided for in Art. 64 of Law no. 94/1992II . We want to analyse the relationship between the Court of Auditors and the auditee, considering the fact that although the audit institution orders measures to recover alleged damages, the exclusive power to choose such measures pertains to the management of the entity. However, the Court of Auditors may decide to refer the matter to the criminal investigation bodies if the damage is not recovered.